THE DEVELOPMENT OF STUDENTS’ VOCABULARY THROUGH EXTENSIVE READING - Sri Vitayanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2014)
Now daysit is very important to master English well, extensive reading can be used to improve thebasic four skills of the students’. This research aimed to investigate to what extent the studentsdeveloped their vocabulary through extensive reading.The research was an experimental study. The total of 76 IPS students participanting in the researchwere devided into two groups. 38 IPS 1 students were treated as the experimental group andanother 38 IPS 2 students were treated as the control group. The experimental group was requiredto do extensive reading, while the control group asked to perform intensive reading. The researchdata were collected through a pre-test and post-test in vocabulary.The research result revealed that the students treated using the extensive reading technique couldsignificantly improve their vocabulary compared to those students treated using the traditionalmethod or the intensive reading technique. This could be seen as follows: (1) the mean value thestudents obtained in the pre-test was 75.93 and in the post-test was 89.93; (2) the T-test value of44.61 was greater than the t-table value of 2.024 (44.61 > 2.024). Besides, the response of theexperimental group to the questionaires was positive about the extensive reading method.